2017
DOI: 10.1007/s00266-017-0803-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BTXA on Inhibiting Hypertrophic Scar Formation in a Rabbit Ear Model

Abstract: This journal requires that authors assign a level of evidence to each submission to which Evidence-Based Medicine rankings are applicable. This excludes Review Articles, Book Reviews, and manuscripts that concern Basic Science, Animal Studies, Cadaver Studies, and Experimental Studies. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The findings of this meta-analysis are supported by the findings from previous studies and reviews of the literature. Liu et al [36] and Fanous et al [37], showed botulinum toxin type A inhibited hypertrophic scars and keloids in animal models. A literature review published by Austin et al [38] also showed that botulinum toxin type A had the potential to prevent pathological scar formation in patients with a known individual history or family history of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this meta-analysis are supported by the findings from previous studies and reviews of the literature. Liu et al [36] and Fanous et al [37], showed botulinum toxin type A inhibited hypertrophic scars and keloids in animal models. A literature review published by Austin et al [38] also showed that botulinum toxin type A had the potential to prevent pathological scar formation in patients with a known individual history or family history of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…A hypertrophic scar is a clinically common skin fibroplasia disease that is caused by an excessive healing response of the human body to trauma (1). It is characterized by the abnormal proliferation of fibroblasts, abundant collagen synthesis and excessive collagen deposition (2). It was recently reported that the incidence of hypertrophic scars in burn patients in China reached 90% (3).…”
Section: Introductionmentioning
confidence: 99%
“…The major effects of BTX include inhibition of muscle contraction and chronic inflammatory stimuli, which consequently reduces scar formation [6][7][8]28]. Moreover, a recent study showed that BTX injections inhibited the formation of HSs and collagen fibrils in a rabbit ear model [20].…”
mentioning
confidence: 99%